EFFECTS OF BIOFLOC AND PHOTOPERIOD MANIPULATION COMBINATION ON BLOOD STRUCTURE OF Pangasianodon hypophthalmus - Surbakti, Yuli Anggreani Putri Br; Windarti, Windarti; Eddiwan, Eddiwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Pangasianodon hypopthalmus can be reared under biofloc system and short photoperiod. To understand the effect of biofloc system and photoperiod manipulation to wards blood structure of P. hypopthalmus a study was conducted on September to December 2020. This experiment using a factorial CRD design with 2 level for B factor (biofloc and no biofloc), 3 level for P factor (Natural, 18 hours dark, 24 hours dark), 3 repetition. The fish was reared in 110L tank, 30 fishes/tank, fed with fish pellet (FF-999, Provit 781-1 and Provit 781-2). Parameters measured were the number of erythrocytes, leukocytes, the level of hematocrit and leukocrite and leukocyte types. The blood was collected using syringe wetted with EDTA 10%. The number of blood cells was calculated using haemocytometer, while the white blood cells were stained using Giemsa solution and checked under a binocular microscope. Results shown that there is no different blood structure in fish of all treatments. Total erythrocytes are 1,681,111-2,647,777 cell/mm3, total leukocytes are 55.031-55.655 cell/mm3, hematocrit 20.33-38.11% and leukocrite 20.33-38.11%. White corpuscle are basophil 00-3.89%, eosinophils 0-3.67%, lymphocytes 26.67-73.89%, trombosit 1-48.89%, monocytes 13.33-30.22% and neutrophill 0.00-9.22%. Based on data obtained, it can be concluded that the biofloc system and photoperiod manipulation combination do not negatively affects the fish hematology.